Nursing care in the chronic alterations of health: perception of students at the senior year of graduation at a public university - Maia, Natália Maria Freitas e Silva; Leite, Cristiane Magalhães; Moreira, Thereza Maria Magalhães (Rev Rene, 2005)
The study aimed at knowing the concept of chronic diseases, the perception of the nursing care by patients with chronic diseases, and the experiences lived by undergraduate students in the care of people who bear such alterations. This descriptive study was developed with 27 students who were in the last year of their major in Nursing at a public university. The results showed that the knowledge of the chronic diseases was related to characteristics of such conditions and their conception and, according to the students, such knowledge was focused on the biological aspect of the health-disease process. In the perception of the nursing care, biological aspects were emphasized, attributing to Nursing the supervision of the compliance with the guidelines provided by the health professional. In the lived experiences, difficulties in specific situations of care were reported, especially in the psychosocial domain. It is necessary that students are better prepared for the coexistence with chronic diseases patients in their professional practice, starting from an amplified understanding of health and of the patients’ participation in the process of taking care.